Aroma volatiles, phenolic profile and hypoglycaemic activity of Ajuga iva L. (August 2020) - Khatteli, Ameni; Benabderrahim, Mohamed Ali; Triki, Tebra; Guasmi, Ferdaous
Abstract: The phenolic profile and aroma volatiles of aerial parts of wild Ajuga iva L., collected from the Tunisian Desert, have been investigated. Sixteen phenolic compounds in the methalonic extract were identified including 7 phenolic acids and 9 flavonoids. The major compounds were cirilisiol (32 ± 2%), chlorogenic acid (2.4 ± 0.1%), cirsilineol (1.6 ± 1%), hyperoside (1.7 ± 0.1%), syringic acid (0.7 ± 0.1%), and quinic acid (0.6 ± 0.1%). The chromatographic analysis showed three volatile compounds detected in hydrodistilled essential oil (HDEO), representing 99% of the total oil, while solid-phase microextraction (SPME) showed 6 components constituting 98% of the volatile material. The results showed that monoterpenes β-pinene (70 ± 5%) and α-pinene (20 ± 2%) were predominant in SPME and β-pinene (59 ± 4%) and limonene (26 ± 4%) were predominant in HDEO. Furthermore, the in vivo anti-diabetic effect of the extract of A. iva aerial parts was monitored. As a supplement at 50% of extract seemed to be beneficial for significantly reducing hyperglycemia ( 4 fold), after 8 days in rats. Graphical abstract: Image 1 Highlights: Phenolic compounds in A. iva were screened using chromatography (LC-MS). Aroma volatiles from leaves were identified using gas chromatography (GC-MS). Monoterpenes were predominant with more than 98% of the volatile material. A. iva extracts significantly reduced glycaemia in diabetic rats.